Characterization of quality differences of Ophiopogonis Radix from different origins by TLC, HPLC, UHPLC-MS and multivariate statistical analyses. Issue 9 (21st July 2022) - Jiang, Ling; Qiu, Yixing; Chen, Zhuliang; Luo, Lu; Tang, Hongxia; Zhou, Xudong; Yuan, Hanwen; Wang, Wei; Liu, Pingan
Abstract: Ophiopogonis Radix is normally used as a traditional medicine and healthy food in China. Thin-layer chromatography (TLC), total saponin content analysis, high-performance liquid chromatographic (HPLC) fingerprinting, ultra-high-performance liquid chromatographic (UHPLC) tandem mass (MS) spectra and multivariate statistical analyses were used to analyze differences in quality of Ophiopogonis Radix from three main producing areas in China. The TLC spots of samples obtained from Zhejiang were clearer and darker than samples from Sichuan and Shandong. Additionally, HPLC fingerprinting analysis of 14 common peaks of the Ophiopogonis Radix samples indicated that the similarities of the 15 batches of samples were between 0.94 and 0.99. Finally, UPLC-Orbitrap MS analysis was used to identify the 13 common peaks of Ophiopogonis Radix . These results showed that Ophiopogonis Radix obtained from different regions can be distinguished well using a combination of analytical techniques, based on differences in their chemical components. The combination of these techniques allows comprehensive and reliable quality evaluation of Ophiopogonis Radix . This study provides references for determining the quality of Ophiopogonis Radix obtained from different regions, which will guide its use as medicine or food. GRAPHICAL ABSTRACT: UF0001